Communicative sabotage, suicide and avoidance as evidences of communicative discomfort: Based on modern Ukrainian plays - Koroliova, Valeria; Hurko, Olena; Popova, Iryna; Holikova, Nataliia; Maiboroda, Nataliia (Linguistics and Culture Review, 2021)
Purpose of the study: The purpose of the article is to compare and distinguish between the communication phenomena of sabotage, suicide, and avoidance displayed in the speech of characters of modern Ukrainian plays; to define them as communicative tactics that do not always violate communicative comfort and lead to conflict in communication; to characterize the main communicative goals and maxims affected by these communicative tactics. The key methods of the study, in addition to general scientific ones, were such dedicated linguistic methods as contextual and situational, speech and action analysis of communicative sabotage, suicide, and avoidance, as well as the method of structural and pragmatic analysis to provide characteristics of speech abnormal behavior of characters in modern Ukrainian plays, to identify of the consequences of communicative sabotage, suicide, and avoidance. The tactics violating the rules of the communication code are communicative sabotage, communicative suicide, and communicative avoidance. Communicative sabotage is mainly used by characters in a negative psychoemotional state as a way to express irritation and contempt, which causes changes in the focus of communication and hinders the achievement of the objective, informative and communicative goals of communication.